PENERAPAN PENDEKATAN METAPHORICAL THINKING PADA PEMBELAJARAN MATEMATIKA SISWA KELAS VIII SMP - Radiatun Radiatun; Rani Refianti; Lucy Asri Purwasi (LP4MK STKIP PGRI Lubuklinggau, 2022)
This study aims to determine the ability of mathematical reasoning in learning mathematics after applying the Metaphorical Thinking learning model. The population was all students of class VIII SMP Negeri 7 Lubuklinggau consisting of 215 students and as a sample were students of class VIII.3, totaling 32 students. Data collection was carried out using test techniques, in which tests were carried out to find out how the mathematical reasoning abilities of class VII students of SMP N 7 Lubuklinggau had been applied using the metaphorical thinking approach to learning mathematics. After conducting an analysis using the t-test at a significant level of α = 5%, it was found that the tcount was 4.19 with a ttable of 1.69 or tcount ≥ ttable. Based on the results of data analysis, it can be concluded that the Metaphorical Thinking model is very well used in learning mathematics. after participating in learning using the Metaphorical Thinking learning model the average post-test score was 71.88 with a percentage of 25% or 8 students who were very good and 62.5% or 20 students who were already good.